The Influence of Pandemic COVID-19 on the Quality of Public Railway Transport in South Bohemia - Telecký, Martin; Papouskova, Kveta (Periodica Polytechnica Transportation Engineering, 2023)
The way the pandemic COVID-19 affecting the public railway transport in the South Bohemia currently is a much-debated issue. On both a theoretical and practical level, this paper aims to determine whether the pandemic COVID-19 influenced the quality of public railway transport in South Bohemia between the years 2020 and 2021. The results of the paper provide the unambiguous arguments which could have been foreseen. There is, however, dissatisfaction among individual groups of passengers as well as on the part of the state. The surveys point to the slowly improving state of the quality of public railway transport in the coming years. Statistical and mathematical methods confirm the overall weaker efficiency and stability of passenger transportation. The reason is the psychological and economic aspects due to the COVID-19 pandemic.